Novel Melt‐Castable Energetic Pyrazole: A Pyrazolyl‐Furazan Framework Bearing Five Nitro Groups. Issue 5 (4th October 2016) - Dalinger, Igor L.; Suponitsky, Kyrill Yu.; Pivkina, Alla N.; Sheremetev, Aleksei B.
Abstract: Continuing advances in energetic pyrazole construction foster further its rational use. This work establishes an approach for the first synthesis of nitropyrazole that bear both furazan and trinitromethyl moieties. The approach to the installation of the C(NO2 )3 group exploits the destructive nitration of N‐acetonyl group. The target 3‐(3, 4‐dinitro‐1‐(trinitromethyl)‐1H‐pyrazol‐5‐yl)‐4‐methylfurazan (6 ) has promising explosive properties. Abstract :